2013
DOI: 10.1186/1471-2229-13-163
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress in Arabidopsis leaves orients microtubules in a 'continuous’ supracellular pattern

Abstract: BackgroundCortical microtubules form a dynamic network and continuously undergo shrinking (catastrophe), pausing and rebuilding (rescue). The advantage of such a dynamic system is that it may mediate appropriate responses in a short time span. Microtubules are known to play a pivotal role in determining the orientation of the cellulose microfibril deposition in the plant cell wall. The latter is a solid exoskeleton surrounding the protoplast. It forms the physical framework that interconnects most cells and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
7
47
0
Order By: Relevance
“…In a series of live cell imaging experiments it was shown that the subcellular organization of microtubules in pavement cells responds to and aligns with the predicted stress patterns [37 ]. This result was consistent with the results from another recent study that analyzed pavement cell microtubule alignment as a function of stress patterns [40 ]. Given that microtubules and cellulose microfibrils colocalize at indentations [41], and that a cellulose synthase mutant has a pavement cell phenotype [42 ], it is highly likely that these oriented microtubules align cellulose microfibrils that are parallel to stress directions.…”
Section: Developing Plausible Biomechanical Models For Pavement Cell supporting
confidence: 87%
“…In a series of live cell imaging experiments it was shown that the subcellular organization of microtubules in pavement cells responds to and aligns with the predicted stress patterns [37 ]. This result was consistent with the results from another recent study that analyzed pavement cell microtubule alignment as a function of stress patterns [40 ]. Given that microtubules and cellulose microfibrils colocalize at indentations [41], and that a cellulose synthase mutant has a pavement cell phenotype [42 ], it is highly likely that these oriented microtubules align cellulose microfibrils that are parallel to stress directions.…”
Section: Developing Plausible Biomechanical Models For Pavement Cell supporting
confidence: 87%
“…Microtubule orientation and bundling change in the presence of mechanical stresses in growing tissues and can therefore be used as a marker of stress patterns [12][13][14][15][16] . We documented microtubule behaviour in the cells of oi-ab and oi-ad before and after fertilization using lines expressing a GFP (green fluorescent protein) fusion to Tubulin Alpha 6 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The application of external mechanical pressure on growing Arabidopsis leaves triggers MT bundling and creates continuous supracellular MT patterns (Jacques et al, 2013). To monitor MT dynamics in Col and xxt1 xxt2 seedlings expressing GFP-MAP4 under external pressure, we constructed chambers with double-sided tape on glass slides, mounted 3-d-old etiolated seedlings in these chambers, pressed coverslips onto the tape to apply gentle, even pressure, and collected confocal z-series of GFP-MAP4 fluorescence.…”
Section: Cortical Microtubules Are More Sensitive To Pressure and Orymentioning
confidence: 99%
“…In general, cortical MT orientation responds to mechanical signals and can be altered by applying force directly to the shoot apical meristem (Hamant et al, 2008). The application of external mechanical pressure to Arabidopsis leaves also triggers MT bundling (Jacques et al, 2013). Kinesins, including KINESIN-13A (KIN-13A) and FRAGILE FIBER1 (FRA1), have been implicated in cell wall synthesis (Cheung and Wu, 2011;Fujikura et al, 2014).…”
mentioning
confidence: 99%